Numerical modelling of transient soil temperature distribution for horizontal ground heat exchanger of ground source heat pump - Kayaci, Nurullah; Demir, Hakan (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
A ground heat exchanger is the most important part of a ground source heat pump system. Soil properties and ground heat exchanger performance strongly depend on soil temperature profile and vary with time and space. Also, soil temperature profile is a function of heat transfer rate extracted or transferred to soil. Studies in the literature either use the unaffected soil temperature obtained from meteorological data or fail to run for long time periods to obtain a steady periodic soil temperature profile and over-predict the ground heat exchanger performance. Therefore, steady periodic temperature profile should be used for sizing ground heat exchanger for efficient operation of ground source heat pumps for longer periods of time. Experimental studies are carried out on a ground-source heat pump established at Yildiz Technical University, Davutpaga Campus and the newly developed numerical model is validated with experimental results. For the numerical study, the hourly required heat load of a 200 m(2) office in Istanbul during the heating season is calculated by using HAP software. The transient soil temperature profile is obtained numerically for longer periods of time with realistic boundary conditions using meteorological data. The fluid inlet temperatures equivalent to the hourly need for heating load of the office during the heating season are simulated for a ten-year period in accordance with the different heat amounts extracted from unit pipe length in soil (21, 10.5 and 7 W/m). The effects of burial depth, distance between pipes and surface effects on soil temperature are also investigated. Horizontal and vertical temperature distribution in soil at the beginning (November 10th), middle (January 21st) and end (April 3rd) of the first, fifth and tenth years are represented.
Keywords: Transient heat transfer; Energy use in building; Ground source heat pump; Buried pipes; Horizontal ground heat exchanger; BURIED PIPE; PERFORMANCE; SYSTEM; SURFACE; SIMULATION; FLOW; Energy & Fuels; Geology